GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP IBU TERHADAP KEJADIAN DIARE PADA ANAK DI PUSKESMAS TIRTOMOYO I WONOGIRI - Ambarwati, Retno; Ratnasari, Nita Yunianti; Purwandari, Kristiana Puji (Akademi Keperawatan Giri Satria Husada Wonogiri, 2018)
The aims of this research are to describe knowledge level and mothers response within diarrhea case in child at Tirtomoyo Community Health CenterÂ IÂ WonogiriÂ regency 2018. Diarrhea is loss of body fluids in 24 hours with the frequency of defecation more than 3 times a day. These symptoms are manifestations of gastrointestinal system infections that can be caused by various types of bacteria, viruses and parasites. This infection can spread through contaminated food or drink or direct infection between humans. The impact of diarrheal disease on children is very influential in the hope of growth and development of children due to frequent loss of fluids and disruption of the process of absorption of food and nutrients needed by children for growth can even lead to death in children. The research is used is descriptive metode with so member of population are 30 people with choosing sampel â€œpurposive samplingâ€ and use queestionare to collec the data. In this study, information needed through primary data, namely data obtained by means of visits to the location of the study and distributing questionnaires to be filled by the respondents themselves. The population in this study were all mothers who had children and came for treatment at the Tirtomoyo I Community Health Center Wonogiri regency.. The samples in the study were a number of mothers who came to seek treatment at the Tirtomoyo I. Health Center. The reseach results of the Knowledge study wereÂ 18 of respondents (22%) with good knowledge, 26 of respondent (32%)with sufficient knowledge, and 36 respondent (45%) with less knowledge. The Result of attitude were 29 of respondent (36%) have good attitudes, 33 of respondent (41%) have sufficient attitudes, and 18 of respondent (22%)have less knowledge. The refor knowledge and motherâ€™s respond within diarrhea case in child is very important to decrease and minimize rate of diarrhea case.Morbility and mortality on child.